Penerapan Konsep Green Technology melalui Lampu Jalan Tenaga Surya di Lingkungan RT 07 RW 01 Desa Sidabowa Kabupaten Banyumas - Slamet Indriyanto; Jafaruddin Gusti Amri Ginting; Zein Hanni Pradana (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
The application of renewable energy technologies is an important strategy to support sustainable development at the community level. This community service program aimed to implement the concept of green technology through the installation of solar-powered street lighting in RT 07 RW 01, Dusun Sidasari, Sidabowa Village, Banyumas Regency. The program employed a participatory and appropriate technology–based approach, in which community members were actively involved in all stages of the activity, including planning, implementation, and evaluation. The implementation stages comprised site surveys and location mapping, coordination with local partners, socialization and education on solar energy utilization, collaborative installation of solar street lights, and evaluation through questionnaire-based surveys. The results indicate that all stages of the program were successfully conducted and received very positive responses from the community. Based on the satisfaction survey involving 20 respondents, the majority strongly agreed that the program was relevant to community needs, provided tangible benefits, and enhanced public understanding of renewable energy utilization. This community service activity not only produced renewable energy–based street lighting infrastructure but also fostered greater awareness and participation among community members in supporting clean energy adoption and the achievement of the Sustainable Development Goals (SDGs).